Improving Mathematical Connection Ability Through Discovery Link Map - Marsitin, Retno; Sesanti, Nyamik Rahayu (Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to analyze the improvement of students' mathematical connection skills through the application of discovery link maps. This research is a quantitative descriptive study. Research with integral material. Data collection includes observations, questionnaires, and tests which are then analyzed descriptively. The results showed that the implementation of discovery link map learning can improve students' mathematical connection abilities. Students' connection skills in remembering mathematical concepts and linking mathematical concepts better through discovery link maps